Secondary mutations in BRCA2 associated with clinical resistance to a PARP inhibitor. Issue 3 (25th January 2013) - Barber, Louise J; Sandhu, Shahneen; Chen, Lina; Campbell, James; Kozarewa, Iwanka; Fenwick, Kerry; Assiotis, Ioannis; Rodrigues, Daniel Nava; Filho, Jorge S Reis; Moreno, Victor; Mateo, Joaquin; Molife, L Rhoda; et al.
Abstract PARP inhibitors (PARPi) for the treatment of BRCA1 or BRCA2 deficient tumours are currently the focus of seminal clinical trials exploiting the concept of synthetic lethality. Although clinical resistance to PARPi has been described, the mechanism underlying this has not been elucidated. Here, we investigate tumour material from patients who had developed resistance to the PARPi olaparib, subsequent to showing an initial clinical response. Massively parallel DNA sequencing of treatment‐naive and post‐olaparib treatment biopsies identified tumour‐specific BRCA2 secondary mutations in olaparib‐resistant metastases. These secondary mutations restored full‐length BRCA2 protein, and most likely cause olaparib resistance by re‐establishing BRCA2 function in the tumour cells. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.